PHYTOCHEMICAL ANALYSIS OF THE CRUDE EXTRACTS OF MONODORA MYRISTICA SEED - EZEUDO EWUZIEM NWAOZUZU, (International Journal of Pharma and Bio Sciences, 2015)
Monodora myristica is one of the plants used as antimalarial remedies in Ibo-Nigeria folkloric medicine which is claimed to possess antimicrobial properties. It has been reported to possess high antifungal properties which have been confirmed by the authors in preceding preliminary studies. The seed of the plant yields a colorless volatile oil which has a pleasant taste and aroma. As such it is used as a condiment for soup. It is added into snuff as a flavouring agent. The seeds are also used to treat migraine by external application to the fore-head. It is used as a stomachic and by mixing it with palm-oil and also as a stimulant. Pomade made from the pulverized seeds fried in oil as well as the powder is used to treat Guinea worm and other sores. This study was designed to ascertain the phytochemical constituents of Monodora myristica seed. Monodora myristica seeds were sun-dried, milled and extracted by cold maceration with 95% methanol. Aqueous solutions of this methanolic extract were then used to conduct various phytochemical tests. The result showed the presence of glycosides, sterols, triterpenoids, aldehydes and unsaturated compounds. The study concluded that the constituents of Monodora myristica may be triterpenoids existing as steroidal aglycones or glycosides.